People's Parliament? An assessment of public participation in South Africa's legislatures - Waterhouse, Samantha Jane (Department of Public Law, 2015)
This paper assesses the political impact of the constitutional framework and policy for public participation in South Africa. I consider the question of how legislatures are fulfilling their obligations to facilitate public participation, if they meet international human rights law (IHRL) norms and the extent to which the public involvement facilitated by legislatures measures up to standards identified by theories of political participation. Central to this is a discussion of whether government-led citizen participation processes influence, or have the potential to influence, state decision-making. I examine the political tensions that arise between public participation and party politics within the context of South Africa's political system and discuss the role of civil society-led participation, and the interactions and conflicts between this and the government facilitated processes.